Structured Parallel Programming: patterns for efficient computation : Michael McCool, Arch D Robison, James Reinders, Morgan Kaufmann-Elsevier 2012 - De Giusti, Armando Eduardo (2015)
In this book the authors, who are parallel computing experts and industry insiders, describe how to design and implement maintainable and efficient parallel algorithms using a pattern-based approach. They present both theory and practice, and give some specific examples using multiple programming models.